Multifunctional porous membranes with antibacterial properties. Issue 1 (11th February 2019) - Stodolak-Zych, Ewa; Dzierzkowska, Ewa; Matwally, Sara; Mikołajczyk, Maciej; Gajek, Marcin; Rapacz-Kmita, Alicja
Abstract: The paper describes the results of research on obtaining porous membranes produced from polylactide fibers (PLA) by electrospinning, additionally modified with gentamicin antibiotic (GM) at the stage of preparing a spinning solution to provide bactericidal properties. Both solid (1 o PNF) and porous (2 o PNF 3 o PNF) polymer fibers were obtained, and the control of fiber porosity was achieved using various solvent systems: dichloromethane (DCM), dimethylformamide (DMF), chloroform (CHL) and dimethyl sulfoxide (DMSO). Three types of fibers differing in morphology (fiber diameter) and mean pore size were obtained. Physicochemical properties of porous and solid drug-containing fibers were examined, determining their surface free energy (SFE) and wetting angle (CA), and the effectiveness of modification with the drug was confirmed in spectroscopic studies (FTIR-ATR). Antibacterial activity of the prepared drug-modified nonwovens was confirmed by the disk diffusion method against Gram-negative Escherichia coli bacteria strain. The results of tests have shown that depending on the type of solvents used at the electrospinning stage, porous fibers can be obtained from polylactide. The addition of gentamicin affected antibacterial properties, and the pore size determined the rate of drug release monitored by the ion coupled plasma method (ICP). Graphical Abstract: